(untitled) (Journal of Contemporary Philology, 2021)
This paper focuses on the representations of the Devil/Satan in Salman Rushdie’s The Satanic Verses, José Saramago’s The Gospel According to Jesus Christ and Mikhail Bulgakov’s The Master and Margarita in order to examine the roles that the satanic principle plays within the unorthodox and even openly blasphemic architectonics of novels which function as profane rewritings of the religious tradition and sacred scriptures of Christianity and/or Islam. Destabilizing the orthodox imagology of Satan as ethically evil and God’s ‘Adversary’, the chosen novels reinscribe the satanic as an expression of the ‘impure’ and differential aspect of identity, language and knowledge. In positing a satanically diversified ontology, ethics and epistemology, Rushdie’s, Saramago’s and Bulgakov’s novels appropriate the satanic as an essentially artistic or literary principle aimed against the monologic and suppressive discourses that conform to the oppressive logic of the One.